Effects of plant regulators on germination of seeds - Castro, Paulo R.C.; Gonçalves, M. Bernadete; Demétrio, Clarice G.B. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1985)
This research deals with the effects of exogenous growth regulators on germination of seeds of several plants. To study the influence of the chemicals, Zea mays, Crotalaria juncea, Lablab purpurcus, Arachis hypogeae, Setaria anceps, Brachiaria humidicola. Stylosanthes sp . , Macroptilium a tropurpurcum , Tefrosia candida, Neonotonia wightti and Panicum maximum seeds were immersed during 22 hours in water solutions of (2-chloroethyl ) trimethylammonium chloride (CCC) 2000 ppm, succinic acid - 2,2-dimethylhydrazide (SADH) 4000 ppm, gibberellic acid (GA) 100 ppm, indoIylacetic acid (IAA) 100 ppm, 6-furfurylaminopurine (FAP) 100 ppm, and water ascheck treatment. GA increased germination of Brachiaria, Macroptilium, Neonotonia and green panic. GA also promoted a more rapid growth of Crotalaria, Lablab and Stylosanthes seedlings. IAA application increased growth of Stylosanthes seedlings; GA and IAA also increased the leaf number of these plants. Soaking Lablab and peanut seeds in SADH reduced the growth of the seedlings. FAP treatment reduced the growth of corn and Lablab plants and increased the growth of Stylosanthes.